2012
DOI: 10.1111/j.1442-2050.2012.01332.x
|View full text |Cite|
|
Sign up to set email alerts
|

Lapatinib, a dual inhibitor of epidermal growth factor receptor and human epidermal growth factor receptor 2, potentiates the antitumor effects of cisplatin on esophageal carcinoma

Abstract: Epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) overexpression occurs in over 30% of esophageal carcinomas. Combination therapies of EGFR- and HER2-targeting agents with cytotoxic agents are considered a potential therapeutic strategy for esophageal cancer. The antitumor effects of lapatinib, a dual tyrosine kinase inhibitor of EGFR and HER2, cisplatin alone, and the combination of the two drugs on esophageal cancer cells were evaluated. The growth inhibition activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Because numerous studies have shown increased cisplatin sensitivity after inhibition of EGFR, HER2/neu or VEGFR in different tumor entities, we performed combination assays despite the relative resistance of our investigated cell lines towards AEE788 [74,75]. Even with low sensitivity towards AEE788 in salivary adenoid cystic carcinoma, cisplatin efficacy was enhanced by AEE788 [76].…”
Section: Discussionmentioning
confidence: 99%
“…Because numerous studies have shown increased cisplatin sensitivity after inhibition of EGFR, HER2/neu or VEGFR in different tumor entities, we performed combination assays despite the relative resistance of our investigated cell lines towards AEE788 [74,75]. Even with low sensitivity towards AEE788 in salivary adenoid cystic carcinoma, cisplatin efficacy was enhanced by AEE788 [76].…”
Section: Discussionmentioning
confidence: 99%
“…The important role of NRF2 in chemoprevention and cellular defense has been clearly demonstrated in NRF2 -null mice which are susceptible to both oxidative and carcinogenic insults [28–31]. Accumulating evidence from both animal models and human epidemiological studies has shown that many naturally occurring phytochemicals, including sulforaphane, epigallocatechin-3-gallate (EGCG), curcumin, and oridonin, possess chemopreventive potential by inducing NRF2-mediated antioxidant/detoxification enzymes [3234].…”
Section: Discussionmentioning
confidence: 99%
“…The methylthiazolyldiphenyl‐tetrazolium bromide (MTT) assay was done as previously described to assessed the sensitivity of cells to drugs . The IC 50 was calculated from survival curves using the Bliss method .…”
Section: Methodsmentioning
confidence: 99%
“…The methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay was done as previously described to assessed the sensitivity of cells to drugs. 18 The IC50 was calculated from survival curves using the Bliss method. 19 The results from the assays were analyzed for the combination effect between ZOL and cisplatin according to the Zheng-Jun Jin method.…”
Section: Cytotoxicity Testmentioning
confidence: 99%